STUDI OPTIMALISASI RUANG PARKIR JL. PATTIMURA KOTA PADANG - Kevin Milano; Ishak Ishak; Ana Susanti Yusman (Ensiklopedia Research and Community Service Review, 2022)
Jalan Pattimura is one of the roads that has many activity centers, such as shopping centers, sports facilities, schools and places of worship. Besides there are many activity centers, side barriers on Jalan Pattimura are quite high. This study aims to determine the availability of parking spaces, the number of vehicles parked and the utilization of parking spaces on Jalan Pattimura. The research method used in this study is to use quantitative and qualitative data, which were surveyed visually. Based on the results of the study, the percentage of parking space for four-wheeled vehicles on Jalan Pattimura on Saturdays and Sundays exceeds 100%. For two-wheeled vehicles on Jalan Pattimura there is no parking space available on the road, on peak days many two-wheeled vehicles use four-wheeled vehicle parking lots. It can be concluded that if the parking index is more than 100%, the available parking space is less efficient in accommodating parked vehicles. The lack of optimization of parking spaces on Jalan Pattimura is also influenced by the lack of implementation of existing parking policies, so that there are still many people who park their vehicles carelessly when parking capacity is still available. In order for the use of parking spaces to be more effective, drivers should be able to park their vehicles in the parking spaces provided. Keywords :Parking, parking space, optimization, Padang